The Implementation Of Content Management On Instagram @Cirengls_Official Social Media Account In 2024 - Hafiz, Haifan Azfa Nur; Junipriansa, Donni (Universitas Ibn Khladun Bogor, 2024)
You can use Instagram as a popular promotional tool by uploading photos and videos. It is also an online facilitator, allowing marketing strategies to introduce brands to the public by building social bonds with users. To optimize sales, Cireng LS uses a social media marketing platform. This study aims to investigate the implementation of content management strategies on the Instagram social media accounts @cirengls_official 2024, encompassing aspects such as sharing, optimization, management, and engagement. This study employs a qualitative exploratory research method, focusing on the Cireng LS consumer population, specifically those who follow @Cirengls_Official. The owner of Cireng LS, the managing partner of @cirengls_official's Instagram account, is the sample for this study. We randomly selected two Cireng LS consumers who follow the @cirengls_official Instagram account and expressed their willingness to serve as informants. Data collection techniques include interviews, observations, and documents. The study's findings indicate that digital marketing on Instagram accounts @cirengls_official has a positive impact on company development. It is essential to understand and apply the principles of marketing communication, creative branding, social media, and digital content marketing comprehensively when formulating an effective branding strategy. It can be inferred that digital marketing on Instagram accounts @cirengls_official positively impacts production cost efficiency and enhances marketing performance. Instagram accounts @cirengls_official produce content that is able to build emotional attachment with customers, play a role in sharing information and product updates, optimize branding and advertising, and also serve as a means of communication with consumers.